Advances in Celiac Disease - Rodrigo, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The incidence of gluten-related disorders (GRDs) continues to increase and its global prevalence is estimated affect to 5% of the population. s. Celiac disease (CD), Dermatitis Herpetiformis (DH), Gluten Ataxia (GA), wheat allergy (WA), and Non-Celiac Gluten Sensitivity (NCGS) are the five major GRDs that present with a wide range of clinical manifestations. They are manifested by symptoms of gastrointestinal tract disorders, as well as hematological, dermatological endocrinological, gynecological, rheumatological and nervous system. NCGS is a term that is used to describe individuals who are not affected by celiac disease or wheat allergy, yet they have intestinal and/or extra-intestinal symptoms related to gluten ingestion with improvement of their symptoms upon withdrawing gluten from their diet. It is believed that represents some heterogeneous groups with different subgroups characterized by different etiologies, clinical histories and clinical courses. There also appears to be an overlap between NCGS and irritable bowel syndrome (IBS). There is a need for establishing strict criteria for diagnosing NCGS. The absence of validated biomarkers remains a significant limitation for research studies on NCGS. New evidence shows that a gluten-free diet may be beneficial for some patients with gastrointestinal symptoms, such as those symptoms commonly found in patients with IBS.